1982
DOI: 10.1159/000112658
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Binding of Serotonin by Primary Cultures of Mouse Astrocytes

Abstract: Primary cultures of glia contain a high glial fibrillary acidic protein level and exhbit important glutamine synthetase activity. They take up serotonin via a high affinity carrirer-mediated system with a Km of micromolar range. The Km of this transport process does not vary during cell growth or maturation; however, during the last period of morphological change induced by dibutyryl cyclic AMP, an increase in Vmax is observed. Chlorimipramine, fluoxetine and fenfluramine at 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1

Year Published

1983
1983
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 15 publications
1
14
1
Order By: Relevance
“…Although astrocytes express receptors for neurotransmitters (6,(15)(16)(17)(18)(19) and contain systems for neurotransmitter uptake (3-7), they do not appear to synthesize neurotransmitters themselves. With the exception of the amino acid transmitters, it is generally accepted that neurotransmitters in brain are localized within neurons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although astrocytes express receptors for neurotransmitters (6,(15)(16)(17)(18)(19) and contain systems for neurotransmitter uptake (3-7), they do not appear to synthesize neurotransmitters themselves. With the exception of the amino acid transmitters, it is generally accepted that neurotransmitters in brain are localized within neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Proliferation of astrocytes plays an integral part in the healing of brain injury, and interactions between neurons and astrocytes regulate neuronal differentiation and process elongation (9-13). Studies of cell surface molecules expressed by astrocytes have shown at least two identifiable subtypes (14), and there is some evidence that there are differences among astrocytes from different regions of the brain (10).Although astrocytes express receptors for neurotransmitters (6,(15)(16)(17)(18)(19) and contain systems for neurotransmitter uptake (3-7), they do not appear to synthesize neurotransmitters themselves. With the exception of the amino acid transmitters, it is generally accepted that neurotransmitters in brain are localized within neurons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Serotonin may regulate the mRNA expression of different GATs by a common intracellular pathway since the percentage of mRNA increase was similar for each transporter. Two main pathways may be involved, either a direct intracellular action of 5-HT via astrocytic 5-HT uptake (Anderson et al, 1992;Kimelberg and Katz, 1985;Tardy et al, 1982) or an effect via 5-HT receptors and second messenger pathways. There is growing evidence that intracellular second messenger pathways can modulate GABA transport, as shown in glial cell cultures (Clark and Amara, 1993;Gomeza et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is also supported by the low levels of Gls activity found by Patel et al 18 in rat cerebellum during the first week of postnatal life when a large proportion of neuroblasts are replicating and by the data of other authors in cultured astrocytes cells. 14,19 The rapid increase, on a per cerebellum basis, of the capacity to take up Gin during the first postnatal week, when cell division occurs at a moderate rate, might correspond to the necessity to accumulate nucleic acid precursors before the burst of multiplication of EGL cells during the second postnatal week.…”
Section: Discussion [3h]gln Influx During Cerebellar Developmentmentioning
confidence: 99%